High‐resolution capillary zone electrophoresis and mass spectrometry for distinction of undersialylated and hypoglycosylated transferrin glycoforms in body fluids. Issue 1 (23rd October 2019) - Caslavska, Jitka; Schild, Christof; Thormann, Wolfgang
Abstract: High‐resolution capillary zone electrophoresis is used to distinguish transferrin glycoforms present in human serum, cerebrospinal fluid, and serum treated with neuraminidase and N‐glycosidase F. The obtained data are compared to mass spectrometry data from the literature. The main focus is on the analysis of the various asialo‐transferrin, monosialo‐transferrin, and disialo‐transferrin molecules found in these samples. The features of capillary zone electrophoresis and mass spectrometry are reviewed and highlighted in the context of the analysis of undersialylated and hypoglycosylated transferrin molecules. High‐resolution capillary zone electrophoresis represents an effective tool to assess the diversity of transferrin patterns whereas mass spectrometry is the method of choice to elucidate structural identification about the glycoforms. Hypoglycosylated transferrin glycoforms present in sera of alcohol abusers and normal subjects are structurally identical to those in sera of patients with a congenital disorder of glycosylation type I. Asialo‐transferrin, monosialo‐transferrin and disialo‐transferrin observed in sera of patients with a type II congenital disorder of glycosylation or a hemolytic uremic syndrome, in cerebrospinal fluid and after treatment of serum with neuraminidase are undersialylated transferrin glycoforms with two N‐glycans of varying structure. Undersialylated disialo‐transferrin is also observed in sera with high levels of trisialo‐transferrin.